A territorialidade da criminalidade violenta no bairro Jardim das Oliveiras – Fortaleza/CE - Freitas, Fabiano Lucas da Silva (2010)
The city of Fortaleza has been facing a progressive increase in the process of socioterritorial segmentation. Territoriality such as condominiums, shopping malls and territorialized conflicts among social groups are part of the same context, the increase of violence in Brazilian cities. Territorialized conflicts seem to multiply throughout the metropolis of Ceará, reaching other cities. Lately, neighborhoods that have shown a high rate of violence in Fortaleza are spaces with strong territorial fight. Fake identities over the years lead to rivalries, feud, revenge and other materialized feelings in those territories prevailing violence and fear. As to a more effective approach to the issues addressed, this research aims at studying the conflicts developed in the neighborhood of Bom Jardim, located southeast of the city of Fortaleza-CE. According to data from CEVEPI/SMF, in 2006, Bom Jardim was the second most violent concerning the variable murder. In this neighborhood, deaths have been the result of territorial clashes among microgroups belonging mainly to Trancedo Neves e Tasso Jereissati. Jardim das Oliveira is not considered a “closed” or “homogeneous” neighborhood concerning identity, but a mosaic of territory with their territorialities. This paper also argues that the assault or committed violence by youth has a remarkable socioterritorial dynamic. In the specific case of violent criminality, it seems to be a marked concentration by gender, race, marital status and age. Being so, young black and/or brown people of stigmatized areas are the main victims of homicides in the city of Fortaleza.